Dual functionality of Trichoderma: Biocontrol of Sclerotinia sclerotiorum and biostimulant of cotton plants - Silva, Lucas Guedes; Camargo, Renato Cintra; Mascarin, Gabriel Moura; Nunes, Peterson Sylvio de Oliveira; Dunlap, Christopher; Bettiol, Wagner (Frontiers in Plant Science, 2022)
Microbial crop protection products based on Trichoderma have the ability to display multifunctional roles in plant protection, such as; pathogen parasitism, enhance nutrient availability and stimulate plant growth, and these traits can be used to enhance the overall agronomic performance of a variety of crops. In the current study, we explored the multifunctional potential of two indigenous Brazilian strains of Trichoderma (T. asperelloides CMAA 1584 and T. lentiforme CMAA 1585) for their capability of controlling Sclerotinia sclerotiorum, a key plant pathogen of cotton, and for their ability of growth promotion in cotton plants (Gossypium hirsutum). Both strains were able to solubilize mineral phosphorus (CaHPO4), to release volatile organic compounds that impaired the mycelial growth of S. sclerotiorum, and to promote the growth of cotton plants under greenhouse conditions. In dual culture, Trichoderma strains reduced the growth rate and the number of sclerotia formed by S. sclerotiorum. By treating sclerotia with conidial suspensions of these Trichoderma strains, a strong inhibition of the myceliogenic germination was observed, as a result of the marked mycoparasitic activity exerted on the sclerotia. The parasitism over S. sclerotiorum was more effective with T. asperelloides CMAA 1584, whilst the effect of biostimulants on cotton growth was more pronounced with T. lentiforme CMAA 1585 that also showed a higher capacity of phosphate solubilization. Thus, T. asperelloides CMAA 1584 displays higher efficiency in controlling S. sclerotiorum, while T. lentiforme CMAA 1585 is more suitable as a biostimulant due to its ability to promote cotton plants growth. Overall, these Trichoderma strains may be used in mixture to provide both pathogen control and promotion of plant growth, and this strategy will support growers in minimizing the use of synthetic fertilizers and fungicides against white mold in cotton crops.